ECONOMIA SOLIDÁRIA E TRANSIÇÃO SOCIAL: o desafio de produção material da existência humana - FILGUEIRAS, Tássio Carlos Rodrigues (2014)
This work seeks the emergence of the Solidarity Economy in Brazil as an alternative proposal for production of existence due to the loss of formal jobs for workers. The use of new technologies that save labor, work in the productive sectors of the economy and the opening of the internal market to competition with foreign companies resulted in loss of formal jobs and a challenge for workers seek alternatives for the production of their material existence . The solidarity economy is then presented as alternative proposal of another economy, based on values and principles antagonistic to capitalism, given the inability of traditional programs for generating employment and income to solve the unemployment crisis. This proposal gains relief from the encouragement received by intellectuals and rulers and shall be incorporated within the state, trade unions and civil society organizations. Expose the appearance of the phenomenon of solidarity economy, presented mainly by its greatest representative in Brazil. Paul Singer, as this phenomenon is in some of its main tangible in Brazil and Maranhão; investigate how Marx treated the phenomenon of recovered factories and cooperatias, and analyze, under this perspective, what elements in these experiments indicate points of overcoming and limits to the capitalist mode of production.